Mammals that can develop type 2 diabetes have a similarly structured β-sheet amyloid oligomer - Brynn E. LeMasters; Caitlyn R. Fields; Justin P. Lomont; Farzaneh Chalyavi; Kacie L. Rich; Donald S. Stapleton; Sidney S. Dicke; Mark P. Keller; Alan D. Attie; Martin T. Zanni (Proceedings of the National Academy of Sciences, 2026)
Some mammals develop amyloid plaques and type 2 diabetes, much like humans, depending on the sequence of their islet amyloid polypeptide (IAPP). In humans, IAPP forms a toxic oligomer with a parallel β-sheet across residues 23 FGAIL 28 S. Using two-dimensional infrared spectroscopy, we monitor the structure of IAPP from seven different mammals, five of which are from species that can develop type 2 diabetes (ferret, raccoon, cat, baboon, and human) and three from those that do not (hamster, rat, and pig). G24 is isotope labeled to monitor for the presence of the oligomeric β-sheet previously found in human IAPP. For the species that develop type 2 diabetes, their IAPP is cytotoxic, and a β-sheet at G24 is observed during the lag phase prior to fibril formation. In contrast, the species that do not develop type 2 diabetes have nontoxic IAPP, and their IAPP does not form this β-sheet structure. Pig IAPP forms oligomers, but with a different structure that is nontoxic. Thus, an oligomer with a parallel β-sheet at G24 that resembles that of the known human IAPP oligomer correlates with cytotoxicity and propensity for type 2 diabetes. These results indicate that the sequence within the 20 to 29 region of human islet amyloid polypeptide (hIAPP), long known to correlate with type 2 diabetes in mammals, determines the structure and toxicity of an oligomer, supporting the oligomer hypothesis for type 2 diabetes and providing an explanation other than plaque formation for why some mammals develop insulin deficiency in late-stage type 2 diabetes, and others do not.